Unravelling relationships and inferring the biogeographic history of a group of herbaceous bamboos from the Northeast Atlantic Forest ( Piresia : Olyreae: Bambusoideae) - Jesus, Izabela S D; Barreto, Silvia B; Santana de Carvalho, Daniel; Schnadelbach, Alessandra S; Carvalho, Maria Luiza S (Botanical journal of the Linnean Society, 2025)
Phylogenies with complex evolutionary histories commonly reflect different evolutionary processes that genes and species may undergo, especially groups with low internal resolution, such as Piresia, a South American herbaceous bamboo genus. Diversification in Piresia is probably recent and associated with hybridization, polyploidization, sympatric speciation, and tropical forest dynamics, creating intricate phylogenetic relationships with paraphyletic and/or cryptic species. In this study, we compare phylogenies generated from six different molecular markers to better estimate and understand the relationships within the genus Piresia, focusing on species from the Atlantic Forest (AF), including the paraphyletic taxa P. leptophylla. We also applied a biogeographic approach to understand the processes influencing the evolutionary history of Piresia. The biogeographic analyses reveal that Piresia originated during the Pliocene and diversified in the Pleistocene, probably influenced by climatic fluctuations. Our results indicate that there is a phylogenetic disjunction between Amazonian and AF species, and low phylogenetic resolution within the latter. Besides, the phylogenetic results retrieved the evolutionary history of Piresia based on the AF lineages (AFI, AFII, AFIII) for the Atlantic Forest.